piRNA-like small RNAs are responsible for the maternal-specific knockdown in the ascidian Ciona intestinalis Type A - Satoh, Teruki (Sci Rep, 2018)
The mRNAs stored in eggs are crucial for embryogenesis. To address functions of maternal mRNAs, we recently reported the novel method MASK (maternal mRNA-specific knockdown), which we used to specifically knockdown maternal transcripts in the ascidian Ciona intestinalis Type A. In MASK, the cis element of a maternal gene is fused with eGFP or Kaede reporter gene, and the cassette is introduced into Ciona genome by transposon-mediated transgenesis. In eggs of the transgenic lines, the maternal expression of the gene whose cis element is used for driving the reporter gene is suppressed. The zygotic expression of the gene is not suppressed, suggesting that the MASK method can distinguish between maternal and zygotic functions of a gene. Here we investigated the cis and trans factors responsible for MASK results. In the ovaries in which knockdown of a maternal gene occurs, a number of antisense small RNAs are expressed that are complementary to the sequence of the knocked-down genes. We suspect that these antisense small RNAs are the factor responsible for MASK results. The antisense small RNAs have several features that are seen in PIWI-interacting RNAs (piRNAs), suggesting that MASK is likely to use a piRNA-mediated mechanism to knock down maternal mRNAs.